2019
DOI: 10.1038/s41598-019-56072-z
|View full text |Cite
|
Sign up to set email alerts
|

Dual action of amitriptyline on NMDA receptors: enhancement of Ca-dependent desensitization and trapping channel block

Abstract: Although the tricyclic antidepressant amitriptyline (ATL) is widely used in the clinic, the mechanism underlying its high therapeutic efficacy against neuropathic pain remains unclear. NMDA receptors (NMDARs) represent a target for ATL and are involved in sensitization of neuropathic pain. Here we describe two actions of ATL on NMDARs: 1) enhancement of Ca2+-dependent desensitization and 2) trapping channel block. Inhibition of NMDARs by ATL was found to be dependent upon external Ca2+ concentration ([Ca2+]) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 70 publications
(113 reference statements)
7
33
1
3
Order By: Relevance
“…To overcome this contradiction, one may suggest an existence of different mechanisms of TCA-inhibition of NMDARs. In agreement, we have recently demonstrated that regardless of the openchannel block, ATL additionally induces a calcium-dependent and voltage-resistant inhibition of NMDARs since the increase of calcium concentration in the extracellular solution substantially enforces the NMDAR inhibition by ATL (Stepanenko et al, 2019). Some similar effects on NMDARs could be achieved by ethanol (Boikov et al, 2020) and lithium or by an inhibitor (KB-R7943) of Na + / Ca 2+ -exchangers (Sibarov et al, 2015), which all as known can provoke the calcium-dependent desensitization of NMDARs (Sibarov et al, 2015).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…To overcome this contradiction, one may suggest an existence of different mechanisms of TCA-inhibition of NMDARs. In agreement, we have recently demonstrated that regardless of the openchannel block, ATL additionally induces a calcium-dependent and voltage-resistant inhibition of NMDARs since the increase of calcium concentration in the extracellular solution substantially enforces the NMDAR inhibition by ATL (Stepanenko et al, 2019). Some similar effects on NMDARs could be achieved by ethanol (Boikov et al, 2020) and lithium or by an inhibitor (KB-R7943) of Na + / Ca 2+ -exchangers (Sibarov et al, 2015), which all as known can provoke the calcium-dependent desensitization of NMDARs (Sibarov et al, 2015).…”
Section: Introductionsupporting
confidence: 81%
“…To obtain the voltage-dependence of NMDAR block by TCAs, the concentration-ihibition curves were generated at three membrane holding potentials V m = −100, −70, and −30 mV. The obtained values were fitted with the modified by incorporating the dependence of NMDAR inhibition on [Ca 2+ ] (Stepanenko et al, 2019) Woodhull equation:…”
Section: Analysis Of Membrane Currentsmentioning
confidence: 99%
“…It also acts to block Ca 2+ and Na + channels (Brau et al, 2001;Nicholson et al, 2002;Yan et al, 2010;Wu et al, 2012). Additional actions of AMI are described for the NMDA receptor ion channel complex that may contribute to efficacy against neuropathic pain, including the enhancement of Ca 2+ -dependent receptor desensitization and acting as an open channel blocker of NMDARs (Stepanenko et al, 2019 0.63 mM (Stepanenko et al, 2019). These actions on the NMDA receptor provide a likely mechanism for results showing that AMI inhibited the NMDA-dependent LTP in the hippocampus (Watanabe et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Cilnipidine was used as a positive control. 30 The test compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) were chosen based on a number of criteria. Firstly, the TCAs examined by Lavoie et al (1)(2)(3)(4) were included.…”
Section: Biological Assaysmentioning
confidence: 99%
“…Five other TCAs, doxepin (7), protriptyline (8), opipramol (9), maprotiline (10) and amoxapine (11), were chosen as these drugs are commonly prescribed tricyclic antidepressants in Australia 31 and the United States 32 and/or Europe. Finally, two structurally-related drugs, the muscle relaxant cyclobenzaprine (12) and the sedating antihistamine promethazine (13) were also tested. The purpose of choosing a wide set of TCAs for study was to gauge the generality of the Ca V 2.2 blockade by this class of drug and to look for any obvious structure-activity relationships.…”
Section: Biological Assaysmentioning
confidence: 99%